(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The collapse of the Fundão dam on November 5th 2015 caused impacts along the hydrographic basin of Rio Doce. Renova Foundation has the mission to repair, restore and reconstruct the regions affected by this disaster. After the collapse, a huge amount of waste was deposited in Risoleta Neves Hydroelectric Power Plant’s lake (Candonga). This waste has been dredged out from the lake and deposited in a nearby pile. The use of the waste from this pile is being considered for civil construction. Samples of this waste pile were collected and they were characterized by X-rays diffraction and EDS analyses, which showed that it consists of 80% quartz, 11% hematite, 8% goethite and 1% clays, mainly kaolinite. There is also organic matter consisting of branches, roots and leaves of trees and plants. Previous radiological analyses made before the collapse showed that the radionuclide content of the waste deposited in Fundão dam was very low. However, the waste deposited in Candonga’s lake has a new composition and it is important to evaluate its radioactivity assessment. The analyses results of the Candonda’s waste samples will be presented and compared to the results obtained in the Fundão dam samples, before its collapse.